2007
DOI: 10.1017/s0007114507336829
|View full text |Cite
|
Sign up to set email alerts
|

Serum prohepcidin concentration: no association with iron absorption in healthy men; and no relationship with iron status in men carrying HFE mutations, hereditary haemochromatosis patients undergoing phlebotomy treatment, or pregnant women

Abstract: Serum prohepcidin concentration: no association with iron absorption in healthy men; and no relationship with iron status in men carrying HFE mutations, hereditary haemochromatosis patients undergoing phlebotomy treatment, or pregnant women Hepcidin plays a major role in iron homeostasis, but understanding its role has been hampered by the absence of analytical methods for quantification in blood. A commercial ELISA has been developed for serum prohepcidin, a hepcidin precursor, and there is interest in its po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
4
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 30 publications
7
60
4
3
Order By: Relevance
“…Furthermore, Nagashima et al reported that serum levels of prohepcidin negatively correlated with levels of ferritin in patients with viral hepatitis C, while this correlation was positive in patients with viral hepatitis B and healthy controls [23]. On the other hand, in other studies serum levels of prohepcidinwere reported as unrelated with ferritin or other iron parameters [24,25]. In our study, no significant difference in serum levels of ferritin was found between healthy controls and patients with AS.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Furthermore, Nagashima et al reported that serum levels of prohepcidin negatively correlated with levels of ferritin in patients with viral hepatitis C, while this correlation was positive in patients with viral hepatitis B and healthy controls [23]. On the other hand, in other studies serum levels of prohepcidinwere reported as unrelated with ferritin or other iron parameters [24,25]. In our study, no significant difference in serum levels of ferritin was found between healthy controls and patients with AS.…”
Section: Discussioncontrasting
confidence: 56%
“…Serum levels of ferritin increases as acute phase reactant in AS. Hepcidin is known to be closely associated and positively correlated with ferritin [9,18] but there are also reports of correlation between prohepcidin and ferritin levels [17,[23][24][25]. A positive correlation was demonstrated between serum levels of prohepcidin and ferritin in chronic renal failure [17].…”
Section: Discussionmentioning
confidence: 98%
“…Because of concerns that a urine assay would not be accurate in CKD, the first published studies in CKD used serum prohepcidin as a surrogate for bioactive hepcidin (22)(23)(24). Prohepcidin was found to be elevated in patients with CKD and inversely correlated with GFR (23-25); however, prohepcidin had minimal interaction with iron or inflammatory parameters in CKD (23,24,26,27) and patients without CKD (28,29). This may be explained by prohepcidin being an intermediate metabolite without physiologic activity.…”
Section: Hepcidin Levels In Ckdmentioning
confidence: 99%
“…It is not clear whether the serum prohepcidin level measures the active hepcidin or whether there is a functional precursor. Changes in the level of serum prohepcidin have been reported to fail to reflect the iron status exactly (11,19,20). Serum prohepcidin levels were not found to be statistically significant difference compared to the control group in patients with high ferritin levels with hereditary hemochromatosis and sickle cell anaemia (19,20).…”
Section: Discussionmentioning
confidence: 92%
“…Changes in the level of serum prohepcidin have been reported to fail to reflect the iron status exactly (11,19,20). Serum prohepcidin levels were not found to be statistically significant difference compared to the control group in patients with high ferritin levels with hereditary hemochromatosis and sickle cell anaemia (19,20). Similarly, Kulaksiz et al (11) did not find any relationship of serum prohepcidin levels with serum iron, transfer saturation, and serum ferritin levels.…”
Section: Discussionmentioning
confidence: 95%